Lipid Levels in Glioblastoma Multiforme and the Role of Ki 67 Index in the Determination of Proliferation Activation - Kaplan, M.; Gercek, E.; Secer, H. I.; Ozer, A.; Yildirim, H.; Akpolat, N.; Koparan, M. (Czech Medical Soc, 2009)
Aims: The aim of this study was to look for an association between lipid levels and the Ki 67 index and the value of the Ki 67 index in the determination of proliferative activity in glioblastoma multiforme (GBM). Materials and methodology: Sixteen patients with GEM who had undergone surgical treatment were included in the study. Pre-operative magnetic resonance (MRI) and MRI spectroscopy investigations were performed on all the patients. The lipid levels of all patients were recorded. In pathological investigation, the ratio of the number of cells stained by Ki 67 nuclear staining to the number of all the cells was calculated in terms of a percentage. The association between lipid levels and the Ki 67 index of cases was analysed. Results: There was no significant relationship between age, gender and the Ki 67 index and lipid levels of cases. it was significant to have a value of 350 as the lowest lipid level in GBM. There was no significant relationship between the Ki 67 index and lipid levels. Conclusions: The Ki 67 index has no value in determination of a treatment strategy in cases diagnosed with GEM. Therefore, we do not believe that the Ki 67 index study should be a routine laboratory investigation in cases with GBM.
Keywords: glioblastoma multiforme; Ki 67 index; lipid level; MRI spectroscopy